1990
DOI: 10.1115/1.2930759
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation Rate Model for a Natural Convection Glazed Collector/Regenerator

Abstract: In the present work, a numerical method has been applied to model the water evaporation rate of a glazed collector/regenerator component of an open-cycle absorption refrigeration system. This two-dimensional model calculates local heat and mass-transfer coefficients as part of the solution. The air flow in the glazed channel is driven by the combined buoyancy of both heat and mass transfer (water evaporation). Since the heat and mass-transfer coefficients each depend on both of the driving potentials determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This is the simplest and cheapest arrangement and therefore considered potentially interesting for the greenhouse application where large areas will be required. Following a survey of theories that have been presented in the literature [5,[7][8][9][10][11][12][13][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], it was decided to adopt the theory of Collier [35] which has already been applied successfully by other researchers [7,11,50]. This approach applies heat and mass balance to a differential control volume at some position x from the inlet of the regenerator to formulate an ordinary differential equation, the solution to which gives an expression for the rate of evaporation per unit area of the surface.…”
Section: Regeneratormentioning
confidence: 99%
“…This is the simplest and cheapest arrangement and therefore considered potentially interesting for the greenhouse application where large areas will be required. Following a survey of theories that have been presented in the literature [5,[7][8][9][10][11][12][13][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], it was decided to adopt the theory of Collier [35] which has already been applied successfully by other researchers [7,11,50]. This approach applies heat and mass balance to a differential control volume at some position x from the inlet of the regenerator to formulate an ordinary differential equation, the solution to which gives an expression for the rate of evaporation per unit area of the surface.…”
Section: Regeneratormentioning
confidence: 99%
“…The dryer is covered with ordinary window glass layer of 3 mm thickness which is used as a transparent cover for the solar dryer to reduce the top heat losses. In addition, the glass cover has many operational and performance advantages as reported by Nelson and Wood (1990). The glazing protects the black-coated bed from rain, birds, insects, dust and reduces contamination by other environmental sources.…”
Section: Experimental Setup and Procedures Experimental Setupmentioning
confidence: 99%
“…For the natural convection type, the performance can be at the mercy of random wind flow direction. However, studies [126] have indicated that the water evaporation rate can be relatively higher in comparison to the open-type because the reduction in the heat losses can increase the solutions temperature and vapour pressure sufficiently to overcome the associated reduction in the mass-transfer coefficient. Nevertheless, McCormick et al [127] have reported that there exists an optimal glazing height, beyond which the system performance becomes similar to that of the open-type variant.…”
Section: Solar Collector Regenerator With Natural Convection and Forcmentioning
confidence: 99%